Evaluating connecting Al-mukha new wind farm to Yemen power system - Majid Manea Manea Albarashi; Doaa Khalil Ibrahim; Essam Eldin Aboulzahab (Cairo : Majid Manea Manea Albarashi, 2015)
This thesis presents modeling and impact analysis of Al-Mukha wind farm (MWF) on Yemen power system. Two simulation studies are carried out; the first is impact on thermal limits, voltage variations, and system stability, with an MWF aggregated model. The other is analyzing low-voltage ride through, harmonics and flicker impact using the detailed MWF layout. The results show that lines loading and voltage variations are slightly reduced and the system stability will not be affected. Although MWF rides-through the grid fault, it contributes harmonics higher than the limits while flicker levels are far below any limits
Thesis (M.Sc.) - Cairo University - Faculty of Engineering - Department of Electrical Power and Machines
Issued also as CD
Keywords: DIgSILENT Power Factory; Doubly fed induction generator; Grid-connected wind farm